2020
DOI: 10.1097/sla.0000000000004230
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Aneurysm Scoring System Predicts Early and Midterm Mortality After Endovascular Repair for Abdominal Aortic Aneurysm

Abstract: Objective: The objective of the study was to develop a better model of prediction after EVAR using the psoas muscle index (PMI). Summary Background Data: The Glasgow Aneurysm Score (GAS), the modified Leiden Score (mLS), the Comorbidity Severity Score (CSS), and the Euro Score (ES) are known prognostic scoring after EVAR. Similarly, sarcopenia measured by PMI has been reported to be an important predictor. This study investigated a new scoring system using PMI predicting short and midterm overall mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Eight articles were excluded and the remaining fifteen studies were found to be eligible for this meta-analysis. [13][14][15][16][18][19][20][23][24][25][26][27][28][29][30] The majority of the studies were retrospective cohort in nature ( There was wide variation in the studies in defining low skeletal muscle mass. All studies measured defined skeletal muscle area by measuring the bilateral psoas muscles with or without additional muscular structures.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles were excluded and the remaining fifteen studies were found to be eligible for this meta-analysis. [13][14][15][16][18][19][20][23][24][25][26][27][28][29][30] The majority of the studies were retrospective cohort in nature ( There was wide variation in the studies in defining low skeletal muscle mass. All studies measured defined skeletal muscle area by measuring the bilateral psoas muscles with or without additional muscular structures.…”
Section: Resultsmentioning
confidence: 99%